Sovereign Wealth Funds: Between the State and Markets - Adam D. Dixon; Patrick J. Schena; Javier Capapé (Agenda Publishing Limited, 2022)
What constitutes a sovereign wealth fund is contested. In general, however, it is a state-sponsored institutional investor that is answerable only to the state and makes investments according to the interests and mandate of that state. Different types of funds have emerged in the context of particular economic conjunctures, and over the last decade the number of sovereign wealth funds has grown substantially, with total assets exceeding 7 trillion. This trend is set to continue, as more and more countries look to establish an SWF. The place of SWFs in global financial markets may appear settled, but this does not mean that concerns about "state capital" and its place in financial markets has gone away. This short book offers an incisive discussion of the development of this class of investor, how they have become legitimate actors in global financial markets, and their role as providers of capital and in economic development at home and abroad.
Keywords: 330; state capital; global finance; financial markets